Average Error: 0.0 → 0.0
Time: 17.6s
Precision: 64
$10^{+30} + \left(x - 10^{+30}\right) \cdot y$
$10^{+30} + \left(x - 10^{+30}\right) \cdot y$
10^{+30} + \left(x - 10^{+30}\right) \cdot y
10^{+30} + \left(x - 10^{+30}\right) \cdot y
double f(double x, double y) {
double r50599102 = 1e+30;
double r50599103 = x;
double r50599104 = r50599103 - r50599102;
double r50599105 = y;
double r50599106 = r50599104 * r50599105;
double r50599107 = r50599102 + r50599106;
return r50599107;
}


double f(double x, double y) {
double r50599108 = 1e+30;
double r50599109 = x;
double r50599110 = r50599109 - r50599108;
double r50599111 = y;
double r50599112 = r50599110 * r50599111;
double r50599113 = r50599108 + r50599112;
return r50599113;
}



# Try it out

Your Program's Arguments

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$10^{+30} + \left(x - 10^{+30}\right) \cdot y$
2. Final simplification0.0

$\leadsto 10^{+30} + \left(x - 10^{+30}\right) \cdot y$

# Reproduce

herbie shell --seed 1
(FPCore (x y)
:name "1e30 + (x - 1e30)*y"
(+ 1e+30 (* (- x 1e+30) y)))